Evolution measuring tape (Ev_Meta-Cx) - Wan Abdullah, Wan Zukri; Bachok, Mohd Fairuz; Nazarudin, Ainamardia; Tholibon, Duratul Ain; Mohd Latib, Farah Wahida (Universiti Teknologi MARA, Kedah, 2023)
The Evolution Measuring Tape (Ev_MeTa-Cx) is an innovative measuring tape that derives inspiration from conventional measuring tapes. One key distinction between conventional tape measures and Ev_MeTa-Cx is the method by which dimensional measurements are obtained. Conventional tape measures rely on manual measurements conducted by users in the field, but Ev_MeTa-Cx simply has to be positioned within the measuring space, after which the space is captured and seen using Ev_MeTa- Cx. The measurement of the object will be obtained by analyzing the image using a specialized smartphone application called ImageMeter. One of the benefits of utilizing Ev_MeTa-Cx is its ability to streamline the process of measuring dimensions, resulting in time and manpower savings. The use of a laser that has been upgraded to be able to detect up to 100 meters further simplifies the measurement work that has been limited so far. This is achieved by simply capturing the spatial information of Ev_MeTa-Cx. There is a significant disparity between the standard tape and the alternative being discussed, particularly in situations where there is a substantial area to be measured and numerous measures are necessary. Moreover, Ev_MeTa-Cx has the ability to detect an infinite number of measurements beyond the constraints of a conventional measuring tape, with the extent of detection being contingent upon the length of the tape. Ev_MeTa-Cx offers the benefit of serving as a gauge, however, its significance lies in its potential as an educational tool for familiarizing students with the application of information technology in the field of measurement. This aligns with the principles of Education Revolution 5.0, Industrial Revolution 4.0, and Sustainable Development Goal (SDG) pertaining to Quality Education.